Peningkatan Kemampuan Berhitung Melalui Permainan Kotak Kelereng di Taman Kanak-kanak Mutiara Ibu Pasir Tiku Agam - Sri Wahyuni; Prima Aulia (RC-INSTITUT, 2020)
This research aims to increase the numeracy skill in playground Mutiara Ibu Pasir Tiku Agam. The type of this research is an action class research, that's is the observation of an intentional activity in the classroom. The qualitative and quantitative data analysis technique user percentage approach in order to get the result of the research. On the first cycle of the three meetings, the development of the numeracy skills research fifty-two percent and it does not fulfill the criteria of the minimal exhaustiveness yet. On the second cycle in the research implementation, there is a very well improvement in the numeracy skill, which is eighty-seven percent and it has fulfilled the criteria of minimal exhaustiveness. The result shows that the marble box game is able to increase the numeracy skill in playground Mutiara Ibu Pasir Tiku Agam.